PENGARUH HIPERTENSI TERHADAP KEJADIAN STROKE: SUATU KAJIAN LITERATUR SISTEMATIS TAHUN 2020–2025 - Ribka Sagala (Bajang Institute, 2025)
Hypertension is a major risk factor for cardiovascular diseases, including stroke. The increasing incidence of stroke worldwide, particularly in developing countries, is often associated with the high prevalence of uncontrolled hypertension. Objective: This study aims to analyze the impact of hypertension on stroke incidence based on scientific evidence from studies published between 2020 and 2025. Methods: This research adopts a Systematic Literature Review (SLR) approach following the PRISMA guidelines. Literature was retrieved from PubMed, ScienceDirect, and BMC databases using the keywords: